Post a New Question


posted by .

Given that lim x->c f(x)=6 and that lim x->c g(x)= -4, evaluate the following limit. Assume that c is a constant. The x in front of the f is confusing me.
lim [xf(x) + 3 g(x)]^2

  • pre-cal -

    The x in front of the f is any constant you would put in the equation.

    Example: x->5 5=c
    lim [xf(x) + 3 g(x)]^2

    so, [5*6 + 5*(-4)]^2

    You should be able to do the rest.

  • pre-cal -

    [c*6 + 3*(-4)]^2 = (6c -12)^2
    = 36c^2 - 144c + 144

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question